Play-Responsive Teaching in Early Childhood Education - Pramling, Niklas; Wallerstedt, Cecilia; Lagerlöf, Pernilla; Björklund, Camilla; Kultti, Anne; Palmér, Hanna; Magnusson, Maria; Thulin, Susanne; Jonsson, Agneta; Pramling Samuelsson, Ingrid (International Perspectives on Early Childhood Education and Development,, 2019)
This open access book develops a theoretical concept of teaching that is relevant to early childhood education, and based on children's learning and development through play. It discusses theoretical premises and research on playing and learning, and proposes the development of play-responsive didaktik. It examines the processes and products of learning and development, teaching and its phylogenetic and ontogenetic development, as well as the 'what' of learning and didaktik. Next, it explores the actions, objects and meaning of play and provides insight into the diversity of beliefs about the practices of play. The book presents ideas on how combined research and development projects can be carried out, providing incentive and a model for practice development and research. The second part of the book consists of empirical studies on teacher's playing skills and examples of play with very young as well as older children.